Risk of Reverse Seroconversion of Hepatitis B Virus Surface Antigen in Rituximab-Treated Non-Hodgkin Lymphoma Patients. Issue 32 (August 2015) - Hsiao, Liang-Tsai; Chiou, Tzeon-Jye; Gau, Jyh-Pyng; Yang, Ching-Fen; Yu, Yuan-Bin; Liu, Chun-Yu; Liu, Jin-Hwang; Chen, Po-Min; Tzeng, Cheng-Hwai; Chan, Yu-Jiun; Yang, Muh-Hwa; Huang, Yi-Hsiang; et al.
<x xml:space="preserve">Abstract</x> Abstract Rituximab causes hepatitis B virus (HBV) reactivation in HBV surface antigen (HBsAg)-seronegative patients with CD20-positive B-cell non-Hodgkin lymphoma (CD20+ NHL), especially for those seropositive to the antibody of core antigen (anti-HBc). Clinical hepatitis usually develops after reverse seroconversion of HBsAg (HBV-RS), indicated by the reappearance of HBsAg in serum. Because of the relatively high prevalence of anti-HBc seropositivity in unvaccinated HBsAg-seronegative adults in an HBV hyperendemic area, we aimed to investigate additional factors influencing the development of rituximab-associated HBV-RS. Between January 2000 and December 2010, unvaccinated HBsAg-seronegative adults with CD20+ NHL who had received rituximab-containing therapy but not anti-HBV agents were enrolled. Patients with and without HBV-RS were compared in terms of clinical factors and treatments including the number of cycles of rituximab therapy, and transplantation. Competing risk regression was used to identify the factors associated with HBV-RS. For the 482 patients enrolled, the serological status of anti-HBc was available in 75.9%, with a seropositivity rate of 86.6%. At the last follow-up, a total of 33 (6.85%) patients had HBV-RS, with 95.8% anti-HBc seropositive, 78.9% anti-HBs seropositive, and none anti-HCV seropositive. HBV-RS patients have received more cycles (≥6) and prolonged durations of rituximab therapy, and hematopoietic stem cell transplantation. The overall survival was not different between patients with and those without HBV-RS. At the time of HBV-RS, a total of 25 (78.1%) patients had hepatitis flare, especially when HBV-RS appeared during/after induction therapy (100%, 10 of 10). Three (9.1%) patients had fulminant hepatitis, resulting in death in 1 (3%) patient. A higher rituximab cycle intensity was associated with a higher rate of hepatitis flare at the time of HBV-RS. When death in the absence of HBV-RS was considered as the competing risk, the univariate and multivariate regression analyses showed that several factors were independently associated with the development of HBV-RS, including anti-HCV seronegativity, histological subtype of posttransplant lymphoproliferative disorders, ≥6 cycles of rituximab therapy, and succeeding hematopoietic stem cell transplantation. The findings of our study identify additional factors influencing the development of rituximab-associated HBV-RS in HBsAg-seronegative adults with CD20+ NHL.